TINJAUAN RASIO RUJUKAN NON SPESIALISTIK PESERTA BPJS DI PUSKESMAS KELURAHAN PONDOK BAMBU PERIODE 2021 - Ahmad Ripki; Laela Indawati; Deasy Rosmala Dewi; Nanda Aula Rumana (Journal of Innovation Research and Knowledge, 2022)
Health Service Facility is a place used to organize health service efforts, whether promotive, preventive, curative or rehabilitative carried out by the government, local government and/or the community. BPJS participants must get a referral first if they want to get services at the destination hospital. Previously, the references used were tiered. BPJS participants must get a referral from the first level of service to get services at the second level and so on. The referral system is organized with the aim of providing quality, effective and efficient health services, so that the goals of health services are achieved without using expensive costs. The author's research method is descriptive quantitative. This study was used to describe the ratio of non-specialist referrals at the Pondok Bamboo Public Health Center with a population of all patients who came for treatment at the Pondok Bamboo Public Health Center in April - June 2021 as many as 2265 patients with a total sample of 99 patients. The results of the study found that the SOP for non-specialist referrals did not exist, so far the SOP for non-specialist referrals refers to the SOP for referrals in general. The average ratio of non-specialist referrals in the village health center of Pondok Bamboo village is 13.6%. The variables that affect the ratio are inadequate infrastructure, limited medicines and medical equipment. The most referred non-specialist diseases were Essential (primary) hypertension (I10) with 13 referrals and the least referred diseases were Seborrhoeic dermatitis, unspecified (L21.9) as many as one referral.